Anatomy of the Anterior Root Attachments of the Medial and Lateral Menisci: A Quantitative Analysis. (October 2014) - LaPrade, Christopher M.; Ellman, Michael B.; Rasmussen, Matthew T.; James, Evan W.; Wijdicks, Coen A.; Engebretsen, Lars; LaPrade, Robert F.
Background: While the biomechanical importance of the meniscal roots has been demonstrated, the anatomy of the anterior meniscal roots remains largely unknown. Defining the quantitative anatomy of the anterior meniscal root attachments is essential for developing improved diagnostic and surgical techniques. Hypothesis: The anterior medial (AM) and anterior lateral (AL) meniscal roots could be quantitatively defined relative to open and arthroscopic surgical landmarks. Study Design: Descriptive laboratory study. Methods: Twelve nonpaired human cadaveric knees were used (average age, 51.3 years). A coordinate measuring device quantified the anatomic relationships of the AM and AL root attachments to open and arthroscopic surgical landmarks. The tibial attachments of both anterior roots were defined and quantified by categorizing the fibers of the root as either central, dense attachments or peripheral, supplemental attachments. Results: The center of the tibial tuberosity and the medial tibial eminence apex were 27.0 mm lateral and distal and 27.5 mm posterior to the center of the AM root, respectively. The center of the anterior cruciate ligament (ACL) and the lateral tibial eminence apex were 5.0 mm posteromedial and 14.4 mm posterolateral to the center of the AL root, respectively. The AM root attachment had a mean area of 110.4 mm 2 (95% CI, 92.2-128.5) with a central attachment of 56.3 mm 2 (95% CI, 46.9-65.8). The AL root attachment had a mean area of 140.7 mm 2 (95% CI, 121.6-159.8) and inserted deeply beneath the ACL in all specimens. The overlap of the ACL on the AL root averaged 88.9 mm 2 (95% CI, 63.3-114.6), comprising 63.2% of the AL root attachment. Conclusion: The anterior meniscal roots were identified in relation to pertinent open and arthroscopic landmarks. The extended overlap between the AL root and ACL attachment revealed a more intimate tibial attachment relationship than previously recognized. Clinical Relevance: Quantitative descriptions of the anterior meniscal roots elucidate the relationship between the root attachments and pertinent surgical landmarks. In addition, the supplemental attachments of both menisci may contribute to native meniscal function, and further investigation is recommended.